Rethinking local spectral modelling: From per-query refitting to model libraries - Leonardo Ramirez-Lopez; Maxime Metz; Matthieu Lesnoff; Claudio Orellano; Estefania Perez-Fernandez; Marcal Plans; Timo Breure; Thorsten Behrens; Raphael Viscarra Rossel; Yi Peng (Analytica Chimica Acta, 2026)

When spectral libraries are too complex to search: Evolutionary subset selection for domain-adaptive calibration - Leonardo Ramirez-Lopez; Raphael Viscarra Rossel; Claudio Orellano; Laurens Kooijman; Estefania Perez-Fernandez; Alexandre M.J.-C. Wadoux; Marcal Plans; Timo Breure; Laura Summerauer; José L. Safanelli; Thorsten Behrens; Ricard Boqué (Analytica Chimica Acta, 2026)

A Systematic Review and Characterization of the Major and Most Studied Urban Soil Threats in the European Union - Hannah Binner; Piotr Wojda; Felipe Yunta; Timo Breure; Andrea Schievano; Emanuele Massaro; Arwyn Jones; Jennifer Newell; Remigio Paradelo; Iustina Popescu Boajă; Edita Baltrėnaitė-Gedienė; Teresa Tuttolomondo; et al. (Water, Air, & Soil Pollution, 2024)
There is an urgent need by the European Union to establish baseline levels for many widespread pollutants and to set out specific levels for these under the Zero pollution action plan. To date, few systematic reviews, superseded by bibliometric analyses, have explored this issue. Even less research has been carried out to compare the efficacy of these two data extraction approaches. This study aims to address these two issues by i) constructing an inventory of the available information on urban soils, highlighting evidence gaps and measuring compliance with the Zero pollution action plan, and by ii) comparing the methods and results of these two data extraction approaches. Through Scopus and Web of Science databases, peer-reviewed articles using the terms urban soil in combination with specific urban soil threats and/or challenges were included. Notably, both approaches retrieved a similar number of initial articles overall, while the bibliometric analysis removed fewer duplicates and excluded fewer articles overall, leaving the total number of articles included in each approach as: 603 articles in the systematic review and 2372 articles in the bibliometric analysis. Nevertheless, both approaches identified the two main urban soil threats and/or challenges to be linked to soil organic carbon and/or heavy metals. This study gives timely input into the Zero pollution action plan and makes recommendations to stakeholders within the urban context.